Proceedings of the 23rd Asian Forum of Business Education(AFBE 2019) 2020
DOI: 10.2991/aebmr.k.200606.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Ratio (Altman Z-Score) on Financial Distress Prediction in Manufacturing Sector in Indonesia 2016-2018

Abstract: This study tries to elaborate the possibility of financial distress in Indonesia public listed companies from manufacturing field. The manufacturing industry was chosen because of its position as a sector that held a significant contribution in the Indonesia industry as a whole. The test tool used to forecast bankruptcy was Altman Z-Score model which consisted of the ratio of net working capital / total asset (X 1 ), retained earnings / total assets (X 2 ), earnings before interest and tax / total assets (X 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Lord et al (2020) also explains that companies with a higher percentage of net assets than total liabilities are better able to overcome financial distress, therefore the ratio of the book value of equity to total liabilities has a significant negative effect on financial distress. This is in line with the results of research conducted by Toly et al (2020) and Altman et al (2014). Referring to the discussion above, we propose hypotheses as follows: H1: Working capital to total assets ratio has a significant negative relationship to financial distress.…”
Section: Accounting Factorssupporting
confidence: 85%
“…Lord et al (2020) also explains that companies with a higher percentage of net assets than total liabilities are better able to overcome financial distress, therefore the ratio of the book value of equity to total liabilities has a significant negative effect on financial distress. This is in line with the results of research conducted by Toly et al (2020) and Altman et al (2014). Referring to the discussion above, we propose hypotheses as follows: H1: Working capital to total assets ratio has a significant negative relationship to financial distress.…”
Section: Accounting Factorssupporting
confidence: 85%
“…One way of dealing with bankruptcy is to use financial analysis to unify companies and provide standards. Until now, several models have been developed as analytical tools that combine several financial indicators and can predict the possibility of a company's financial difficulties (Toly et al, 2020). Ratio analysis is a technique for evaluating a company's financial statements by combining the numbers from the income statement and the results of their tests.…”
Section: Theoritical Reviews a Financial Distressmentioning
confidence: 99%
“…Overall, the results indicated that the financial health of the sample studied needs improvement. Toly et al, (2020) examine Indonesian publicly listed manufacturing companies for the possibility of financial distress. The study uses The Altman Z-Score model to forecast bankruptcy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since development in 1968, Altman's Z-score has been widely used to evaluate the risk of financial failure by companies in various countries, industries, and time-periods. Predicting financial distress using Altman's Z-score is one of the popular methods used as indicated by (Toly et. al., 2020;Ranjbar & Amanollahi, 2018;Abdulkareem, 2015;Cho et al, 2012;Wu, 2010).…”
Section: Introducing the Problemmentioning
confidence: 99%